Intra-accumbal and Peripheral administration of nicotine reduces the side-effects of Inescapable Stress - Hamid Reza Malayeri, Hedayat Sahraei, Hengameh Alibeik, Boshra Hatef, Gholam Hossein Meftahi, Alireza Mohammadi (Journal of Applied Pharmaceutical Science, 2017)
Background: The mesolimbic dopaminergic system plays an important role in controlling the effects of stress. Here, the role of nicotinic receptors in the nucleus accumbens, one of the most important parts of the mesolimbic system in reducing the effects of stress in mice has been studied. Methods: Bilateral intra-accumbal (shell of nucleus accumbens; sNA) cannulation was performed carefully. Animals were allocated randomly into nine groups and received nicotine intra-peritoneally (IP; 0.25, .05, and 1 ml/Kg) and intra-accumbally (sNA; 1, 5 and 10 μg/mouse), respectively. 30 minutes later saline and nicotine injection, the animal received an electric shock stress from the soles of the feet for 60 seconds. The body, brain and adrenal glands weight, food and water consumption and anorexia time were evaluated. Results: The results showed that IP administration of 1 mg/Kg nicotine (IP Nic 1) and intra-accumbal injection of 1 and 5 μg/mouse nicotine (NAc Nic 1 and 5) lead to weight loss. Although, intra-sNA injection of nicotine couldn’t improve the food consumption, but the significant increases in food intake were observed in the IP Nic 1. The water intake increased and the brain weight decreased dose-dependently by rises of nicotine dose. The weight of the adrenal gland was significantly raised in IP Nic groups. Anorexia (decreased appetite), decreased or increased depending on the nicotine dose. Conclusion: We conclude that intra-accumbal nicotine administration reduces the signs of stress in a dose dependent manner, which probably is associated with the role of nicotinic acetylcholine receptors.
Keywords: Stress,Nucleus accumbens,Mesolimbic,Nicotine,Anorexia.